Omentum tranplant for Parkinson´s disease: Report of 3 cases - Hernando Rafael (2013)
Introduction: Since 1990, we have postulated that the primary cause of Parkinson´s disease (PD) is of ischemic origin initiated in the mesencephalic tegmentum. However, up to date, almost all researchers consider that the etiology is unknown. Objetive.To demonstrates that PD can be improved by means of omental transplantation. Material and Method: We present 3 patients with advanced PD. Through a temporal craniotomy we located the carotid bifurcation and anterior perforated space (APS). Here we found: 1) atherosclerosis at the supraclinoid carotids; 2) absence of anterior choroidal or posterior communicating arteries; 3) several exsanguine anterior and posterior perforating arteries,and 4) atherosclerosis at the basilar bifurcation. The omentum was placed on the APS and interpeduncular fossa. Results: Neurological improvement was observed after the third day and evident in the first weeks postoperatively. At present, 10 and 23 months after surgery, two patients require incomplete antiparkinsonian medication and besides, they receive aspirin and clonazepan. All of them carry out daily activity without assistance familiar. Conclusions: Our results indicate that PD is caused by progressive ischemia in the intraparenchymal territory of the posterior perforating arteries; because, in contrast to this, its revascularization by means of omentum produced neurological improvement .Likewise we believe that the regular use of aspirin and clonazepan may help to this disease.